West Africa Climate-Smart Villages AR4D sites: 2017 Inventory - Bonilla Findji, Osana; Ouédraogo, Mathieu; Partey, Samuel T.; Dayamba, Sidzabda Djibril; Bayala, Jules; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
2017 Inventory of CSA practices in West Africa's Climate-Smart Villages.